Teknik Relaksasi Nafas Dalam Pada Ny. M Untuk Menurunkan Skala Nyeri Post Partum Dengan Laserasi Perineum di PKD Kedungjati - Fentri Yuda Antika; Eko Sari Ajiningtyas; Dwi Astuti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background : Parineal lacerations usually accur during early or later labour in the next birth. In 2012, the World Health Organization (WHO) estimates that nearly 90% of parineal laceration accur in normal births. According to (Choirunissa et al., 2019 ). The prevelence of spontaneus child birth in purbalingga regency in 2015 was 92,91 percent compared to 2014 of 99,70 percent with a prevalence of 6,79 percent. 82,91 percent of the lands is owned by the Kutawis Health Center (Purbalingga Distcric Health Profile, 2015). Objectiv : Nursing Influeces With Deep Breathing Relaxtion Techniques To Reduce Pain Scale In Post Partum Patients With Parineal Lacerations at PKD Keungjati. Methods : The case study used a descriptive method, with G1P1A0 gestational age respondents with acute pain nursing problems so that it focused on providing deep breathing relaxation techniques to reduce post partum pain scale with parineal laceration. Result : Deep breathing relaxation techniques can reduce the pain scale by showing that the patient does not complain of pain anymore. Conclusion : The effect of deep breathing relaxation techniques can reduce the scale of spontaneous post partum pain with parineal laceration.